The Influence Of Knowledge Sharing, Technological Capabilities, And Innovation Strategies On The Smes Performance, Mediated By Open Innovation - Syadan Rizqi Tasyrin; Arif Hartono (UNIVED Press, 2025)
SMEs play a very important role in the Indonesian economy, but often face challenges in utilising technology and adopting innovations needed to remain competitive. This study aims to examine the influence of knowledge sharing, technological capabilities, and innovation strategy on SME performance in Yogyakarta, with open innovation as a mediating variable. Using a quantitative approach, this study collected data from 106 respondents who are SME owners and employees who are active in innovation activities. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to test the relationship between variables. The results showed that knowledge sharing has a positive and significant effect on open innovation and SME performance. In addition, technological capabilities are also proven to have a significant effect on open innovation and SME performance. Although innovation strategy has a positive effect on open innovation, its effect on SME performance is not significant. Open innovation was found to have a significant influence on SME performance. This finding indicates that SMEs that are active in knowledge sharing and have good technological capabilities, as well as implementing open innovation, will have better performance. This research provides insights for practitioners and academics in formulating strategies to improve SME performance through strengthening knowledge sharing, technology utilisation, and implementing open innovation.